Role of Technology Management to Enhance Cognitive and Innovative Strategies in an Organization - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
The paper enumerates about the utilization of innovation the board for cutting edge inventive faculty preparing for powerful logical, mechanical, monetary and social advancement of nations, depicting subjective techniques in the 6th and seventh mechanical cycles. Competency building approach in the new arrangement of the 6th innovative cycle requires the control of comprehension process, techniques for making of expansive instruction from data allocated to the subject of learning. Subjective innovations of the 6th mechanical cycle are arranged to unadulterated psychological procedures and have a place with the field of brain science, teaching method and information, while socio-philanthropic advancements allude to the individual, practice, society, morals, ethics, qualities and culture. It shows up in the seventh method for subjectivity condition, subjectivity culture, uncommonly composed and intelligent dynamic condition, making new types of life on the planet. Chronicled conventions of the Russian culture and attitude offer motivations to be one of the main nations to endeavor to get into the seventh mechanical cycle.Â Â